Polypharmacy in patients with multiple sclerosis and the impact on levels of care and therapy units - Brüggemann, Finn; Gross, Stefan; Süße, Marie; Hok, Pavel; Strauss, Sebastian; Ziemssen, Tjalf; Frahm, Niklas; Zettl, Uwe K.; Grothe, Matthias (Frontiers in Neurology, 2023)
Background: The aim of this study was to examine the economic burdensocietal costs of polypharmacy in patients with multiple sclerosis (MS). We therefore focused on the association between the number of medications on the level of care (LOC) as the German classification of the need for care and the amount of therapy sessions (TTU) (number of physical and occupational therapy visits in the last 6 months). Methods: In total, 101 MS patients were included in the study. Besides demographic information and medication, 101 MS patients performed the Multiple Sclerosis Health Resource Utilization Survey (MS-HRS). Medications were subdivided into total number of medications (TD), MS-related medication (MSD, i.e., disease-modifying drugs (DMD) and symptomatic treatment (SD)), and medication for comorbidities (CD). Multivariate linear regression models were performed for both level of care (LOC) and total therapy units (TTU) to estimate if the amount of each medication type significantly affects LOC or TTU. Results: Polypharmacy appeared in 54 patients (defined as ≥5 medications) at the time of the survey. The relative risk (RR) of LOC 1 increased significantly by 2.46 (p=0.001) per TD and by 2.55 (p=0.004) per MSD, but not per CD (RR 1.44; p=0.092). The effect of RR of MSD was driven by SD (RR 2.2; p=0.013) but not DMD (RR 2.6; p=0.4). RR of MSD remained significant for LOC 2 (1.77; p=0.009) and LOC 3/4 (1.91; p=0.015), whereas RR of TD was significant for LOC 2 (1.61; p=0.041) but not for LOC 3/4 (1.57; p=0.06), and RR of CD remained not significant for the higher LOC (LOC 2 RR 1.01; p=0.957; LOC 3/4 RR 0.97; p=0.883)with a strong trend in RR of SD, but not DMD. TTU within the last 6 months increased significantly per MSD (p=0.012), but not per TD (p=0.081) and CD (p=0.724). Conclusion: The total number of MSD is related to the likelihood of a higher level of care and the number of therapy sessions and are therefore a good indication of the extent of economic the societal costs.